2013
DOI: 10.1016/j.jcdr.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Age and clinical outcomes in patients presenting with acute coronary syndromes

Abstract: a b s t r a c tContext: Elderly patients have more cardiovascular risk factors and a greater burden of ischemic disease than younger patients. Aims: To examine the impact of age on clinical presentation and outcomes in patients presenting with acute coronary syndrome (ACS). Methods and material: Collected data from the 2nd Gulf Registry of Acute Coronary Events (Gulf RACE-2), which is a prospective multicenter study from six adjacent Arab Middle Eastern Gulf countries. Patients were divided into 3 groups accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
(32 reference statements)
2
24
0
Order By: Relevance
“…In the present study ST-Segment Elevation Myocardial Infarction was more prevalent among the younger age group in agreement with Stem et al [ 5 ]. Hypertension was commoner among older patients and in agreement with Ahmed et al [ 3 ]. No significant statistical difference was found regarding diabetes mellitus, and prior myocardial infarction one plausible explanation is the closer age ranges in the two subgroups as only 12.6% of our samples were above 70 years old.…”
Section: To the Editors Of The Pan African Medical Journalsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study ST-Segment Elevation Myocardial Infarction was more prevalent among the younger age group in agreement with Stem et al [ 5 ]. Hypertension was commoner among older patients and in agreement with Ahmed et al [ 3 ]. No significant statistical difference was found regarding diabetes mellitus, and prior myocardial infarction one plausible explanation is the closer age ranges in the two subgroups as only 12.6% of our samples were above 70 years old.…”
Section: To the Editors Of The Pan African Medical Journalsupporting
confidence: 90%
“…Furthermore, the expected mortality rate is higher. In spite of the American College of Cardiology/American Heart Association (ACC/AHA) guidelines statement that age should not influence patients cares elderly acute coronary syndrome patients benefit less from evidence-based therapy including interventional procedures [ 3 , 4 ]. There is an increasing awareness of the clinical presentation, ECG, and outcomes of acute coronary syndrome among elderly people due to expanding aging populations [ 5 ].…”
Section: To the Editors Of The Pan African Medical Journalmentioning
confidence: 99%
“…The available results from the OASIS-1 and -2 registries 95 and epidemiologic studies in India 96-98 suggest that earlier age for first ACS in LMICs is a major contributing factor. Registry data from many other LMICs also support the assertion that ACS often occur at younger ages than in HICs: 99-109 Strikingly, a registry from the United Arab Emirates reported a mean age of 50.8 years. 110 Earlier age for first ACS is likely due to earlier acquisition of adverse health behaviors and IHD risk factors 10,97,111,112 in the current context of economic development and globalization.…”
Section: Acs and Ihd Burden In Lmicsmentioning
confidence: 71%
“…Ahmed et al (45) demonstrated that older patients had a higher risk of adverse hospital outcomes and short- and long-term mortality rates with respect to younger patients. As shown in previous studies, we found that renal dysfunction, together with age and PLR, is independently related with inhospital mortality.…”
Section: Discussionmentioning
confidence: 99%